الصورة الشعرية في الخطاب النقدي الأندلسي بين نظرية المحاكاة الأرسطية والبلاغة العربية: ابن رشد وحازم القرطاجني أنموذجاً - ترشاق، سعاد (جامعة زيان عاشور الجلفة, 2017)
The poetic picture is the highlights of the core features and poetry characteristics as reflecting the imagined poetic meanings, and translates the feelings of the creator and embodied, so it won a clear interest by critics, past and present. This research come in an attempt to find out its concept in critical discourse Andalusian by prominent intellectuals namely: (Ibn Rushd) and (Hazem Alqirtagini) for distinguished him from asking a different reverse quality culture that set off them in search of critics, a mixture between the two cultures Arab orients and Greek Aristotelian, How they were able to adapt the concept of the image as it came in Greek with the Arab critics concept? and with the poesy Arab privacy? What are the signs of excellence that the uniqueness of the critics for other critics? And other questions will be the focus of the research.
الصورة الشعرية من أبرز مميزات الشعر وخصائصه الجوهرية إذ تعبر عن معاني المتخيل الشعري، وتترجم مشاعر المبدع وتجسدها، لذلك نالت اهتماما واضحا من طرف النقاد قديما وحديثا. ويأتي هذا البحث محاولة لمعرفة مفهومها في الخطاب النقدي الأندلسي من خلال مفكرين بارزين هما: (ابن رشد) و(حازم القرطاجني) لما تميزا به من طرح مغاير عكس نوعية الثقافة التي انطلقا منها في البحث النقدي، وهي مزيج بين الثقافتين العربية المشرقية واليونانية الأرسطية، فكيف تمكنا من تكييف مفهوم الصورة كما جاءت في النقد اليوناني مع المفهوم العربي لها ومع خصوصية الشعر العربي؟ وما هي علامات التميز التي تفرد بها الناقدان عن غيرهما من النقاد؟ وغيرها من الأسئلة التي ستكون محور اهتمام البحث.
Keywords: الشعر العربي -- الصورة الشعرية -- البلاغة العربية -- الخطاب النقدي الأندلسي -- نظرية المحاكاة الأرسطية -- النقد اليوناني -- ابن رشد -- القرطاجني، حازم